Studi Komunikasi Media Baru Pada Pengguna Aplikasi Konferensi Video Dalam Pembelajaran Daring Di Masa Covid-19 - Clara Owissa Harefa (DIII Prodi Humas Fakultas Ilmu Sosial Universitas Negeri Jakarta, 2022)
The occurrence of the Covid-19 case that entered Indonesia in March 2020 caused community activities that are usually carried out from outside the home such as going to school to be carried out indoors to anticipate the spread of the virus. So the government issued a warrant to implement Distance Learning (PJJ) from home. One of them is Gunadarma University by using new media, namely video conferencing as an intermediary medium between lecturers and students. This study aims to determine the experiences of Gunadarma University students in using video conferencing and to find out the supporting and inhibiting factors in using video conferencing applications in learning activities for students. This type of research is descriptive qualitative using the phenomenological paradigm. By using uses and gratification theory, cognitive learning theory, and new media. The author uses the technique of observation, interviews, and documentation. The results of this study explain that students get new experiences in terms of the learning process by using video conferencing and there are supporting factors in it such as it is easier to take classes anytime anywhere and the inhibiting factors are unsupported devices, limited quota, and constrained network problems. Keywords: New media, video conferencing, uses and gratification theory, cognitive learning theory